The concept of "mind" in the language world of Abai - Bibekov, Қ.Т.; Orazgalieva, Л.М.; Mussabayeva , Г.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article employs the linguo-conceptological approach to analyse the semantic sphere of verbalisation and definition of the "mind" concept in Abai's language. To the best of the present author's knowledge, the concept of "mind" in Abai's works has not previously been the subject of research in Kazakh linguistics. The concept of "mind" in Abai's language is closely connected with the worldview of the Kazakh people, Islamic knowledge, and holds meanings and semantic features unique to the poet's creativity. The linguistic expression of this concept, as evidenced by the employment of terms such as mind, science, thought, eyes, ray, and intellect, is manifested in phrases like "cold mind", "icy cold mind," "radiant mind," "the eyes of mind," "fair mind or righteous reason" and "mind" thereby acquiring a heightened degree of concreteness within the context of the text. The concept of "mind" encompasses qualities such as cognition, science—mastery of knowledge, differentiation of benefit and harm, comparison, verification, analysis, etc. In Abai's linguistic world, the concept of "mind" is measurable. This measurability is not indicative of an inability to perceive the otherworldly, but rather, it is a testament to one's capacity to recognize Allah. Abai highlights the dynamic and evolving nature of the mind.